STUDIES ABOUT MATHEMATICS IN ELEMENTARY SCHOOL VIEWED FROM PREVIOUS AND CURRENT CURRICULUM - Anugrahana, Andri (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2019)
The aims of this study is to describe the position of mathematics learning in the curriculum of Kurikulum 2013 (K13) when compared to the previous curriculum. namely Kurikulum Tingkat Satuan Pendidikan (KTSP). This research is literature study, with a qualitative approach. Data was collected by analyzing the K13 and KTSP. The data source is the curriculum that applies in Indonesia, they are k13 and KTSP for elementary schools. Data analysis was carried out by: (1) analyzing the scope of mathematical material by looking at SK and KD class 1 to grade 6 in the KTSP curriculum and curriculum 2013; (2) looking for differences from each material scope in each class, class 1 to grade 6 in the curriculum K7SP and also the K13; and (3) search for material coverage, namely the concept of numbers, geometry, measurement and statistics in the old and new curriculum in elementary school. The results of the study are (I) The analysis of the scope of material in grades 1 through 6 on the 2013 KTSP and curriculum curriculum; The differences in material coverage at each level is class 1 to grade 6, and (3) Material coverage, namely the concepts ,r1 numbers, geometry, measurement and statistics for the K13 and KTSP ellPtielthlfril for elementary school.